PENGARUH BUDAYA ORGANISASI DAN PENGAWASAN TERHADAP KINERJA MELALUI KOMITMEN KARYAWAN FRONTLINER PT BANK RIAU KEPRI - Kumala Dewi, Indah Sri; Sasmita, Jumiati (Jurnal Tepak Manajemen Bisnis, 2015)
This research aims to determine the influence of organization culture and supervision on the performance through employee commitment in Riau Kepri Bank. The research method used is descriptive. The population in this research are 147 employees customer service. By using a Proportionate Stratified Random Sampling method it has been obtained 106 respondents. Data collected with questionares. Techniques of data analysis is using path analysis.The result show that organization culture have a significant and positif influence on the commitment; supervision have not a significant and negatif influence on the commitment; commitmen have a significant and positif influence on the performance; organization culture have a significant and positif influence on the performance; supervision have not a significant and negatif influence on the performance; influence organization culture to performance through employee commitmen more bigger than influence organization culture on performance; influence supervision to performance through employee commitmen have not give contribution to develope employee performance.Keywords: organization culture, supervision, commitment, and performance.